Analysis of the Influence of the Numerical Relation in Handball During an Organized Attack, Specifically the Tactical Behavior of the Center Back - Prudente, João Nunes; Cardoso, Américo Ramos; Rodrigues, Ana Jose; Sousa, Duarte Filipe (Frontiers in Psychology, 2019)
In the last decades, observational methodology has been widely used in scientific research in sport, namely in the study of team games like handball, due to its characteristics. Handball, in addition to being a collective, complex, dynamic, and interactive sport, has its own characteristics and demands a performance analysis that takes into account the context and interaction between different factors and variables. The present study analyzes how the different numerical relations in an attack can change the center back’s patterns of tactical behavior. Observational methodology and a mixed ad hoc instrument combining field format and category systems appropriately validated by experts were used. Data were taken from 20 matches involving teams classified in the first four places in the 2017 Men’s World Championship. These were recorded from TV broadcasts, and the total number of offensive sequences carried out in an organized attack game method (n = 990) was analyzed. In each of the sequences carried out in an organized attack, the numerical relation in attack or defense was observed and recorded. In addition to this, it was verified whether the attacking team maintained or replaced the goalkeeper by a field player in the attack. Both sequential analysis techniques with lags, prospective, and retrospective, as well as polar coordinate analysis, were used. Results have shown that there are different behavioral patterns of the center back in the three different situations of numerical relation. Another element that stood out was that in numerical equality with the defense and no goalkeeper at the goal, the center back opted for greater security and less risk of loss of the ball.